2020
DOI: 10.9779/pauefd.686232
|View full text |Cite
|
Sign up to set email alerts
|

Affetmeyi Geliştirmeye Yönelik Bir Grup Psikoeğitim Programının Psikolojik Danışman Adaylarının Affetme Düzeylerine Etkisi

Abstract: This research was carried out with a mixed research model to test the group psychoeducation program's effectiveness to improve psychological counselor candidates' forgiveness levels. In this research 2x3 (experiment / control groups-pre-test / post-test / follow-up test) quasi-experimental design was used. Participants of the study consist of 20 psychological counselor candidates; half of them are in the experimental group, and the other half of them are in the control group. The effectiveness of the psychoedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the literature review, intervention programs that were prepared and implemented separately for the variables of optimism (Avcı, 2009), self-compassion (Sarıcaoğlu & Arslan, 2019), altruism (Nedim-Bal & Topuz, 2015) and gratitude (Kocatepe, 2020), It is known that it contributes positively to the development of the relevant characteristics of the participants. In addition, when the experimental studies in the context of forgiveness are examined, it is seen that the intervention programs prepared for forgiveness, although they are planned on different contents, make positive contributions to the forgiveness skills of emerging adults (Bugay & Demir, 2012; Goldman & Wade, 2012; Ji et al, 2016; McCullough, 1995; Parlak & Öksüz-Gül, 2021; Vural-Batık & Afyonkale-Talay, 2021). Based on these evidence-based intervention programs, psycho-educational programs for forgiveness, supported by the personality characteristics of optimism, self-compassion, altruism and gratitude, can be administered to emerging adults in groups of 12–14 within 8–10 sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, intervention programs that were prepared and implemented separately for the variables of optimism (Avcı, 2009), self-compassion (Sarıcaoğlu & Arslan, 2019), altruism (Nedim-Bal & Topuz, 2015) and gratitude (Kocatepe, 2020), It is known that it contributes positively to the development of the relevant characteristics of the participants. In addition, when the experimental studies in the context of forgiveness are examined, it is seen that the intervention programs prepared for forgiveness, although they are planned on different contents, make positive contributions to the forgiveness skills of emerging adults (Bugay & Demir, 2012; Goldman & Wade, 2012; Ji et al, 2016; McCullough, 1995; Parlak & Öksüz-Gül, 2021; Vural-Batık & Afyonkale-Talay, 2021). Based on these evidence-based intervention programs, psycho-educational programs for forgiveness, supported by the personality characteristics of optimism, self-compassion, altruism and gratitude, can be administered to emerging adults in groups of 12–14 within 8–10 sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is observed that many forgiveness interventions have been carried out and that process-based interventions have the most effective results (Baskin & Enright, 2004). In studies conducted to improve forgiveness, it has been revealed that interventions based on the Forgiveness Process Model (Asıcı, 2018;Bugay & Demir, 2012;Ertürk, 2019;Freedman, 2018;Freedman & Knupp, 2003;Hilbert, 2015;Ji, 2013;Vural-Batık & Afyonkale-Talay, 2021) positively affect feelings, thoughts, and attitudes towards forgiveness and contribute to an increase in the tendency to forgive. In the Forgiveness Process Model, it is emphasized that it is a process for an individual to let go of negative feelings, face past experiences and painful feelings, look at the person who hurt him/her from a different perspective and choose to let go of feelings of revenge and anger.…”
Section: Introductionmentioning
confidence: 99%